Formulation and Development of Nanostructured Lipid Carriers for a Poorly Water-Soluble Drug: Furosemide - Jadhav, Abhish B.; Savkare, Anand D.; Gaikwad, Sachin S. (Applied Drug Research, Clinical Trials and Regulatory Affairs, 2022)
Aim: Formulation, development and evaluation of solid lipid nanoparticles. Background: It was found that furosemide (FU) was a very potent drug but it fails to produce bioavailability due to its BCS class IV, so drug- cyclodextrin (CD)- nanostructured lipid carriers (NLC) will be an alternative to improve solubility and permeability as a result of this overall bioavaibility will be improved. Objective: To improve the solubility of drug by using complexation of cyclodextrin. Coating with the lipids (NLC) will improve the permeability of the drug. Methods: To generate solid Furosemide-cyclodextrin complexes (FU-CD), two distinct CDs and three different techniques were used. The co-evaporation (COE) Furosemide-β-cyclodextrinloaded NLC (FU- β-CD-COE-loaded NLC) was obtained by emulsification ultrasonic dispersion method. The selected batch was suitably characterized for particle size, polydispersity index, zeta potential, Entrapment efficiency, Drug release study, and permeability study. The crystallization of the drug in the furosemide cyclodextrin complex (FU-CD complex) and the co-evaporation Furosemide- β-cyclodextrin-loaded NLC (FU-β-CD-COE-loaded NLC) was investigated by differential scanning calorimetry (DSC). The in vitro release study was carried out. Results: The FU-β-CD-COE-loaded NLC and FU-HP-β-CD-COE-loaded NLC (Hydroxypropyl) presented a superior physicochemical property and were selected for further study. The in vitro release study of the above selected batches exhibited a higher dissolution rate in the pH 5.8 phosphate buffer than Furosemide suspension and FU-NLC. The permeability studies of abovementioned batches were compared with FU-Suspension. Conclusion: The novel formulation considerably enhanced the solubility and permeability of furosemide for oral delivery, and was successfully developed.
Keywords: permeability